The legal geographies of extradition and sovereign power - Sally Kennedy (Internet Policy Review)
This paper demonstrates how a request for the extradition of a Canadian citizen accused of online child luring by United States authorities opens up a complex series of domestic legal issues regarding access to, use and exchange of evidence under mutual legal assistance requirements. While these arrangements aim to protect vulnerable child victims from predatory online behaviour, they also skew established notions of due process and the rule of law to favour US sovereignty and criminal enforcement power. We conclude by explaining the impact of these issues on the dynamics of global online criminal investigations.